Therapeutic Treatment Planning for Sex Therapy Using the Sexual Health and Integrative Pleasure (SHIP) Model - Connor, Jennifer Jo; Arenella, Katherine; de Oliveira, Leonor; Evenson, LynAnne; Mark, Kristen P.; Newstrom, Nicholas P.; Robinson, Beatrice "Bean" E.; Vencill, Jennifer A.; Girard, Abby (Journal of sex & marital therapy, 2025)
Treatment plans are an important, ethical, and often required aspect of clinical care for mental health providers, though in many cases can be inconsistent with the aims of sex therapy. Utilizing the Sexual Health and Integrative Pleasure (SHIP) Model as a conceptual framework, we address often overlooked treatment planning considerations in sex therapy. Two detailed case studies are used to demonstrate how the SHIP model can be applied in clinical practice via its 5 main components: sexual adaptation and resilience, sexual literacy, relational intimacy, multidisciplinary care, and pleasure-oriented positive sexuality. We also address the role of systemic, intersectional, empirical, lifespan, and biopsychosociocultural approaches in effective sex therapy treatment. With tangible examples for clinicians to directly apply to their sex therapy practice, this paper provides guidance on an important component of clinical care for which many providers have received limited training.